Quality of life among healthcare workers in the hospitals and primary healthcare centers in Gaza Strip: a cross-sectional study - Joma Younis; Lina Wang; Amal Abed; Hong Jiang; Yahui Fan; Zhaofang Li; Mei Ma; Le Ma; Zhaozhao Hui; Linlin Hua; Wei Zhang (BMC Psychology)
Abstract Background Quality of life (QoL) is an important measure of overall well-being linked to physical, mental, social, and environmental aspects of health. This study aimed to assess the QoL among healthcare workers (HCWs) in hospitals and primary healthcare centers (PHCs) in Gaza Strip, Palestine. Methods A cross-sectional study was conducted among 1850 HCWs in Gaza Strip, Palestine. Data were collected by using self-administered questionnaires in the paper-based format containing a sociodemographic profile and the World Health Organization Quality of Life Brief questionnaire. Factors associated with QoL were examined using an independent t-test, Chi-square test, and multivariate logistic regression models. Results The study included HCWs with a mean age of 38.62 years old, of whom 61.9% were male. The mean QoL score was 55.98 (standard deviation: 11.50), with 55.5% reporting a good QoL. Multivariate logistic regression analysis revealed that age, smoking status, workplace, and work shifts were associated with the overall QoL score (p < 0.05). Older age (≥ 35 years), working in a hospital, and working the morning shifts were identified as protective factors for QoL, while smoking and working the evening-night shifts were inversely associated with QoL. Conclusions This study found that HCWs in Gaza Strip exhibited moderate levels of QoL. Age, smoking status, workplace, and work shifts were associated with overall QoL. Strategies to improve HCWs’ QoL, such as lifestyle interventions, additional support through training or educational programs, and reducing work schedules, could be considered under high-pressure situations.